With risk may come reward: Sensation seeking supports resilience through effective coping. (15th January 2018) - McKay, Samuel; Skues, Jason L.; Williams, Ben J.
Abstract: Sensation seeking is often considered a risk factor for negative psychosocial outcomes. Our research challenges this view, testing a model in which sensation seeking is associated with psychological resilience, with this relationship mediated by coping. Two-hundred-and-sixty-eight respondents completed measures of sensation seeking, experiences of trauma, coping, perceived resilience, subjective wellbeing, and perceived stress. Sensation seeking was directly and indirectly positively associated with the psychological resilience markers of life satisfaction, positive affect, and (lower) perceived stress through problem-focused coping in those who had experienced trauma. Sensation seeking was also positively related to greater perceptions of resilience. Based on the results it is argued that sensation seeking increases resilience by decreasing stress responses and increasing individual's resources to manage adversity. Results highlight the need to consider sensation seeking as a multifaceted construct that can support healthy development through building resilience. Highlights: A model of sensation seeking acting a resource for resilience is proposed. Sensation seeking was positively related to psychological markers of resilience. The sensation seeking and resilience relationship was partially mediated by coping.